2008
DOI: 10.2337/dc07-1810
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Component Profiles and High Risk Among African Americans With Metabolic Syndrome

Abstract: OBJECTIVE -Health of African Americans is seriously threatened by unremitting epidemics of diabetes and cardiovascular disease (CVD). However, the role of metabolic syndrome in the African-American population has not been investigated widely. This study examined the prevalence of metabolic syndrome and assessed its cross-sectional relationship to CVD in the Jackson Heart Study (JHS) cohort.RESEARCH DESIGN AND METHODS -A total of 5,302 participants aged Ն21 years who were recruited at baseline during 2000 -2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
72
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 37 publications
12
72
1
Order By: Relevance
“…We [12,13,35,37] and others [4, 5•, 6-17, 19-23, 47] have reported a weaker association between insulin resistance and triglycerides in African Americans. Furthermore, Sumner et al [22,23] and Haffner et al [4,49] showed that the increasing serum triglycerides are not associated with changes in serum total cholesterol and LDL cholesterol levels in African American women.…”
Section: What Is the Relevance Of The Components In Mets In Blacks?mentioning
confidence: 97%
See 2 more Smart Citations
“…We [12,13,35,37] and others [4, 5•, 6-17, 19-23, 47] have reported a weaker association between insulin resistance and triglycerides in African Americans. Furthermore, Sumner et al [22,23] and Haffner et al [4,49] showed that the increasing serum triglycerides are not associated with changes in serum total cholesterol and LDL cholesterol levels in African American women.…”
Section: What Is the Relevance Of The Components In Mets In Blacks?mentioning
confidence: 97%
“…Apart from body mass index (BMI), WC is reported to be greater predictor of MetS in several populations, although the cut off points vary according to the IDF criteria [31,[33][34][35]. In blacks, WC is the most common component of MetS [11, 14-16••, 18].…”
Section: Paradox Of Insulin Resistance Body Composition and Mets Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ''Other-Bumiputera'' refers to other native ethnic groups, not including the Malays). [14][15][16][17] Ethnic-based disparities in metabolic syndrome prevalence have been noted in previous studies for developed countries, [18][19][20] and reducing inequality among citizens of different ethnic groups has been a long-standing goal of policy makers in Malaysia. Therefore, this study uses data from a nationally representative sample of Malaysians to study differences in metabolic syndrome prevalence, as well as differences in the underlying conditions that comprise metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The Framingham Heart Study has been helpful in identifying traditional cardiovascular risk factors; studies such as the Jackson Heart Study (JHS) have confirmed its utility in African Americans also (Taylor et al, 2008). The JHS found that 40% of African American women, as opposed to 29% of African American men, had the traditional cardiovascular risk factors (Association of American Medical Colleges [AAMC], 2008).…”
Section: The Framingham Heart Studymentioning
confidence: 99%